At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Solve the equation [tex]\(x^2 - 6x + 4 = 0\)[/tex].

The solutions can be written as [tex]\(a \pm \sqrt{b}\)[/tex], where [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are prime numbers. Find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex].


Sagot :

To solve the quadratic equation [tex]\(x^2 - 6x + 4 = 0\)[/tex] and express the solutions in the form [tex]\( a \pm \sqrt{b} \)[/tex], where [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are prime numbers, follow these steps:

### Step 1: Identify the coefficients
The quadratic equation [tex]\(x^2 - 6x + 4 = 0\)[/tex] has the following coefficients:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = -6\)[/tex]
- [tex]\(c = 4\)[/tex]

### Step 2: Calculate the discriminant
The discriminant [tex]\(\Delta\)[/tex] of a quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex] is given by:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Plugging in the values, we get:
[tex]\[ \Delta = (-6)^2 - 4(1)(4) = 36 - 16 = 20 \][/tex]

### Step 3: Find the solutions using the quadratic formula
The quadratic formula to solve [tex]\(ax^2 + bx + c = 0\)[/tex] is:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Substituting the coefficients and the discriminant, we have:
[tex]\[ x = \frac{6 \pm \sqrt{20}}{2 \times 1} = \frac{6 \pm \sqrt{20}}{2} \][/tex]

### Step 4: Simplify the expression
Simplify the solutions:
[tex]\[ x = \frac{6 \pm \sqrt{20}}{2} = \frac{6 \pm \sqrt{4 \times 5}}{2} = \frac{6 \pm 2\sqrt{5}}{2} = 3 \pm \sqrt{5} \][/tex]

### Step 5: Identify [tex]\(a\)[/tex] and [tex]\(b\)[/tex]
The solutions can be written as [tex]\( a \pm \sqrt{b} \)[/tex], where:
- [tex]\(a = 3\)[/tex]
- [tex]\(b = 5\)[/tex]

Both [tex]\(3\)[/tex] and [tex]\(5\)[/tex] are prime numbers. Thus, the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are:
[tex]\[ \boxed{3 \text{ and } 5} \][/tex]

The solutions to [tex]\(x^2 - 6x + 4 = 0\)[/tex] are [tex]\(3 + \sqrt{5}\)[/tex] and [tex]\(3 - \sqrt{5}\)[/tex].
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.